# Lec5 - Lecture 5 18.01 Fall 2006 Lecture 5 Implicit Differentiation and Inverses Implicit Differentiation d Example 1 x a = ax a 1 dx We proved

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Lecture 5 18.01 Fall 2006 Lecture 5 Implicit Differentiation and Inverses Implicit Differentiation d Example 1. ( x a ) = ax a- 1 . dx We proved this by an explicit computation for a = 0 , 1 , 2 , ... . From this, we also got the formula for a =- 1 ,- 2 , ... . Let us try to extend this formula to cover rational numbers, as well: m m a = ; y = x n where m and n are integers. n We want to compute dy . We can say y n = x m so ny n- 1 dy = mx m- 1 . Solve for dy : dx dx dx dy = m x m- 1 dx n y n- 1 ( m We know that y = x n ) is a function of x . dy = m x m- 1 dx n y n- 1 m x m- 1 = n ( x m/n ) n- 1 m x m- 1 = n x m ( n- 1) /n = x ( m- 1)- m ( n n- 1) m n m n ( m- 1)- m ( n- 1) = x n n m nm- n- nm + m = x n n m m n = x n- n n dy m m So, = x n- 1 dx n This is the same answer as we were hoping to get! Example 2. Equation of a circle with a radius of 1: x 2 + y 2 = 1 which we can write as y 2 = 1- x 2 ....
View Full Document

## This note was uploaded on 02/27/2009 for the course MATH 155b taught by Professor Staff during the Fall '08 term at Vanderbilt.

### Page1 / 4

Lec5 - Lecture 5 18.01 Fall 2006 Lecture 5 Implicit Differentiation and Inverses Implicit Differentiation d Example 1 x a = ax a 1 dx We proved

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online